Penerapan Metode Single Moving Average Untuk Peramalan Penjualan Potel Ketela - Wahyuni, Tri; Primadewi, Ardhin; Ully Artha, Emilya (STMIK Budi Darma, 2024)
The Sajen Chips home industry is one of the MSMEs providing various processed chips made from cassava in the Trenten Village area. So far, it has been difficult to predict future product sales. Forecasting sales of cassava potel chips in the Kripik Sajen home industry is needed to make decisions about supplying cassava stock so that it can reduce stock excesses and shortages that often occur. This research uses the Single Moving Average (SMA) method to forecast cassava chips sales in the Kripik Sajen home industry. This research uses a sample of sales reports in October 2022 - October 2023 with movement values ??of 1, 2, 3, 4, 5, 6, 7, and 8 which will be used as calculation data for the Single Moving Average (SMA) method. Calculation of error from forecasting results uses the Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE) methods. So the final results can be obtained after calculating SMA forecasting and calculating MAD and MAPE errors. This research aims to determine the prediction of sales of cassava products by using the movement period and the SMA method. The forecasting results that have been carried out have good accuracy (small error rate) obtained in period 7, namely 108.57 kg of cassava potel sales in November 2023, which have a MAD accuracy of 8.69% and MAPE of 7.98%. These results show that the 7 is the best sales prediction for the Sajen Chips home industry.